Les feux d’artifices des frères Ruggieri à l’intérieur d’un théâtre. L’autonomie de l’éphémère dans le Paris du XVIIIe siècle - De Luca, Emanuele (Status Quaestionis, 2025)
The Ruggieris were a family of pyrotechnicians from Bologna, active in Paris throughout the eighteenth century. On the one hand, they were ‘artificiers du roi de France’ and worked for public celebrations (both in the city and at court), on the other hand, they were crucial for the advancement of pyrotechnics across the Enlightenment. Appointed at Comédie-Italienne, they benefitted from a stimulating environment where actors understood the potential of pyrotechnics, allowing the Ruggieris to bring, indoors in a theater, tricks that had been mainly used for outdoor public celebrations (birth of the Dauphin, trade fairs, peace agreements, etc.). This article traces the history of the Ruggieris’ fireworks by reconstructing the innovations that lent sparkle to the art of pyrotechnics in eighteenth-century Paris. It envisions the ways in which the ephemeral celebration of fire was turned into an ephemeral theatrical experience, subject to the logics of spectacle, but also to repetition and profit.